2008
DOI: 10.1002/biot.200800015
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and ageing in Drosophila

Abstract: Studies in different organisms have revealed that ageing is a complex process involving a tight regulation of gene expression. Among other features, ageing organisms generally display an increased oxidative stress and a decreased mitochondrial function. The increase in oxidative stress can be attributable to reactive oxygen species, which are mainly produced by mitochondria as a by-product of energy metabolism. Consistent with these data, mitochondria have been suggested to play a significant role in lifespan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 137 publications
1
16
0
Order By: Relevance
“…This imbalance can result in extremely large mitochondria because of an increase in fusion rates (Terman et al 2006;Morrow and Tanguay 2008), or conversely a low fusion-to-fission ratio can result in numerous rod-shaped, fragmented mitochondria (Detmer and Chan 2007). Here, examples of both of these types of mitochondrial disruptions are evident in the mushroom body neuropil of 50-wk-old adults.…”
Section: Aging and The Mushroom Bodymentioning
confidence: 88%
See 1 more Smart Citation
“…This imbalance can result in extremely large mitochondria because of an increase in fusion rates (Terman et al 2006;Morrow and Tanguay 2008), or conversely a low fusion-to-fission ratio can result in numerous rod-shaped, fragmented mitochondria (Detmer and Chan 2007). Here, examples of both of these types of mitochondrial disruptions are evident in the mushroom body neuropil of 50-wk-old adults.…”
Section: Aging and The Mushroom Bodymentioning
confidence: 88%
“…That 50-wk-old adults have a significantly greater spine count but noticeably different synapse morphology and apparent frequency, provides strong evidence that not all spines are equipped with functional synapses in this age group. Disruptions to the structure and function of neuronal mitochondria in association with the aging process have been widely reported (for review, see Lin and Beal 2006;Terman et al 2006;Detmer and Chan 2007;Morrow and Tanguay 2008). Specifically, an increase in the size of mitochondria during aging has been suggested to be a consequence of an imbalance between the fusion and fission events that normally Figure 11.…”
Section: Aging and The Mushroom Bodymentioning
confidence: 99%
“…There is a large body of evidence linking an increase in ROS and oxidative stress with the aging process [66, 67]. Mitochondria are a major source of ROS in the cell and mitochondrial function has been found to decline in aging organisms [68].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Drosophila that have manipulated nuclear and mitochondrial genetic variation have found that mitonuclear epistasis is an important force in shaping longevity variation (James and Ballard 2003;Rand et al 2006;Maklakov et al 2006;Ballard et al 2007;Clancy 2008;Dowling et al 2009). Observations that naturally occurring levels of mitochondrial genetic variation could produce substantial variation in longevity shed new light on the mitochondrial theory of ageing (reviewed in Morrow and Tanguay 2008;Bratic and Trifunovic 2010;Kirkwood and Kowald 2012).…”
Section: Introductionmentioning
confidence: 99%